The Redox Homeostasis of Skeletal Muscle Cells Regulates Stage Differentiation of Toxoplasma gondii - Rahman, Md. Taibur; Swierzy, Izabela J.; Downie, Bryan; Salinas, Gabriela; Blume, Martin; McConville, Malcolm J.; Lüder, Carsten G. K. (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasma gondii is an obligatory intracellular parasite that causes persistent infections in birds and mammals including ~30% of the world’s human population. Differentiation from proliferative and metabolically active tachyzoites to largely dormant bradyzoites initiates the chronic phase of infection and occurs predominantly in brain and muscle tissues. Here we used murine skeletal muscle cells (SkMCs) to decipher host cellular factors that favor T. gondii bradyzoite formation in terminally differentiated and syncytial myotubes, but not in proliferating myoblast precursors. Genome-wide transcriptome analyses of T. gondii-infected SkMCs and non-infected controls identified ~6,500 genes which were differentially expressed (DEGs) in myotubes compared to myoblasts, largely irrespective of infection. On the other hand, genes related to central carbohydrate metabolism, to redox homeostasis, and to the Nrf2-dependent stress response pathway were enriched in both infected myoblast precursors and myotubes. Stable isotope-resolved metabolite profiling indicated increased fluxes into the oxidative branch of the pentose phosphate pathway (OxPPP) in infected myoblasts and into the TCA cycle in infected myotubes. High OxPPP activity in infected myoblasts was associated with increased NADPH/NADP+ ratio while myotubes exhibited higher ROS levels and lower expression of anti-oxidants and detoxification enzymes. Pharmacological reduction of ROS levels in SkMCs inhibited bradyzoite differentiation, while increased ROS induced bradyzoite formation. Thus, we identified a novel host cell-dependent mechanism that triggers stage conversion of T. gondii into persistent tissue cysts in its natural host cell type.